2016
DOI: 10.1371/journal.pone.0151903
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Kidney and Liver Tissue Response to Different Hydroxyethylstarch (HES) Preparations in a Rat Model of Early Sepsis

Abstract: BackgroundTissue hypoperfusion and inflammation in sepsis can lead to organ failure including kidney and liver. In sepsis, mortality of acute kidney injury increases by more than 50%. Which type of volume replacement should be used is still an ongoing debate. We investigated the effect of different volume strategies on inflammatory mediators in kidney and liver in an early sepsis model.Material and MethodsAdult male Wistar rats were subjected to sepsis by cecal ligation and puncture (CLP) and assigned to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Causative approaches to explaining these findings remain scarce. Lately, acetate as a common component of available HES formulations has been shown to act as a proinflammatory factor during systemic inflammation in rats [ 57 ]. Furthermore, a recent study showed that high dosages (50 ml/kg) of HES 130/0.4 cause deterioration of kidney function in otherwise healthy rats [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Causative approaches to explaining these findings remain scarce. Lately, acetate as a common component of available HES formulations has been shown to act as a proinflammatory factor during systemic inflammation in rats [ 57 ]. Furthermore, a recent study showed that high dosages (50 ml/kg) of HES 130/0.4 cause deterioration of kidney function in otherwise healthy rats [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The steatotic hepatocytes may be a more important source of proinflammatory cytokines resulting from altered lipid and immune homeostasis [37-39]. Furthermore, a heterogeneous class of hepatokines such as plasminogen activator inhibitor-1 and tumor necrosis factor-α can modulate reversed renal lipid accumulation, glomerular sclerosis, and tubulointerstitial inflammation [40-42]. …”
Section: Discussionmentioning
confidence: 99%
“…For isovolumic haemodilution, 2-ml blood was withdrawn from the venous catheter every 30 min over a 90-min period; during this time the animals remained positioned according to group assignment. Blood was replaced with 6% Hetastarch (Hospira, Lake Forest, Illinois, USA) 12 following each 2-ml blood withdrawal, until target haematocrit (approximately 40% reduction) was achieved.…”
Section: Methodsmentioning
confidence: 99%